Women Empowerment through Production and Online Marketing Training of Wingko Babat Based on Cassava in Baturono Village, Sukodadi, Lamongan - Yudiana Indriastuti; Herlina Suksmawati (Nusantara Science and Technology Proceedings)
Empowering women's groups is seen as one of the specific strategies to increase their abilities and potential. Empowering women in business as an effort to increase independence and internal strength of a woman. Empowering women can also help improve the welfare of families and communities. The women in the village of Baturono, Sukodadi, Lamongan have a great opportunity in exploiting the potential of the village, especially the production of Wingko Babat which is a special food from the area. Wingko Babat production business competition certainly requires them to have innovation to be able to compete in the market. Through community service activities with UPN "Veteran" Jawa Timur, a group of women from the village of Baturono, Sukodadi, Lamongan have received training in producing Wingko Babat based on cassava with the best quality. This innovation was carried out as an effort to bring alternative flavors. In addition, the use of cassava as main ingredient is one of the efforts to maximize the processed products from the village plantations. Furthermore, through online marketing training activities, they have basic knowledge about the use of online media to marketing food products. And also, development model of home industry marketing networks. Until now, assistance activities continue to be carried out as an effort to monitor the development of women's business groups in the village of Baturono, Sukodadi, Lamongan.